PENGARUH MEDIA LABIRIN TIUP TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI TK ARNOLDUS - Elandis Risna Burga (Al Fitrah: Journal Of Early Childhood Islamic Education, 2026)
Social emotional development is an important aspect that must be developed in early childhood because it influences children's ability to interact, cooperate, control emotions, and adapt to the environment. This study aims to determine the effect of inflatable maze media on the social emotional development of children aged 5–6 years at Santo Arnoldus Kindergarten. The study used a quantitative approach with a pre-experimental method through a one group pretest-posttest design. The subjects were 11 children in group B. The data collection technique used observation with a social emotional development assessment sheet instrument. Data were analyzed using a t test. The results of the study showed an increase in children's social emotional development after being given treatment using inflatable maze media. The t test results showed a calculated t value of 24.99 which was greater than the t table of 2.228 at a significance level of 0.05. Thus, it can be concluded that inflatable maze media has a significant effect on the social emotional development of children aged 5–6 years at Santo Arnoldus Kindergarten.